Pengaruh Pola Asuh Orang Tua Terhadap Gaya Hidup Siswa SMA Laboratorium Percontohan UPI - Irawati, Mila; Wahidah, Ananda; Agustine , Puspa Nova (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2020)
Parenting is a process where the children obtain the socialization pertaining to the implementation of norms and values that later on will formulate their personality in maintaining the lifestyle. Thus, the parenting is expected to bring the very positive contribution to children development, good parenting is be bound to the good influence of children pursuing their lifestyle. In fact, teens are pretty much swayed by the modern era that leads to the high life style. A teenager especially student is actually influenced by not only the family but also the peers, school and other environments. It leads to the very high possibility of them to adopt the lifestyle that served within the circumstances. The aim of this research is to employ the amount of influences of the parenting toward the student’s lifestyle of senior high school laboratorium percontohan UPI. This research utilizes the qualitative approach with description method and use the questionnaire as the primer data source. The technique for analyzing data, the research employs the Weight Means Score (WMS). the results shows that the parenting having by the student is categorized as good with the lifestyle also within the level of appropriate and in line with the norms and value. Statistically, the research found that the influence of parenting toward the student life style is 20.5% and environment contributed for the rest.